Algorithms for Automatic Model Topology Formulation - Yongfeng Feng; Mantooth, H.A. (IEEE transactions on computer-aided design of integrated circuits and systems, 2009)
A novel algorithm for automatic behavioral model topology formulation (MTF) is described in this paper. Several new terms are defined to support this formulation approach. The algorithms for determining the controllability and equivalence of branches are developed. The identification of differential pairs and current mirror structures is implemented automatically. Some other algorithms identify a subset of nodes in circuits that are extracted and modeled, while the other nodes will be collapsed. The MTF algorithm then is applied to construct a new signal-path graph, i.e., forming an equivalent circuit that has the ability to represent the behavior of the original circuit in a much-simplified form. This algorithm is implemented in a fully automated modeling tool, ASCEND, which starts from the netlist description of a circuit and generates a differential-algebraic-equation-based model. These models are able to represent static and dynamic behaviors with excellent accuracy and significant simulation speedup. The details of the MTF algorithm are described. Examples of applying the MTF algorithm for behavioral modeling are given.